1997
DOI: 10.1038/bjc.1997.108
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of concurrent whole-brain radiotherapy and chemotherapy combined with cisplatin, vindesine and mitomycin in non-small-cell lung cancer with brain metastasis

Abstract: Summary We have evaluated the feasibility, toxicity, and tumour response of concurrent whole-brain radiotherapy (WBRT) and chemotherapy with cisplatin, vindesine and mitomycin in the treatment of 33 patients with brain metastasis from non-small-cell lung cancer (NSCLC). The imaging response demonstrated that 25 patients (75.8%) responded to brain lesions, including five complete responders, and the response rate to primary lesion was 18%. The treatment improved at least one grade of performance status in 30% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Encouraging evidence of the efficacy and an increase in the local response rate has been obtained in studies of concurrent radiotherapy and chemotherapy with carboplatin only, 17 or combined chemotherapy with CDDP, vinorelbine, and ifosfamide, 18 or combined chemotherapy with CDDP, mitomycin C, and vindesine. 19 The intracranial response rates in these studies were 50%, 75.5%, and 56%, while the median survival times were 5.6, 9.7, and 7.6 a b…”
Section: Discussionmentioning
confidence: 98%
“…Encouraging evidence of the efficacy and an increase in the local response rate has been obtained in studies of concurrent radiotherapy and chemotherapy with carboplatin only, 17 or combined chemotherapy with CDDP, vinorelbine, and ifosfamide, 18 or combined chemotherapy with CDDP, mitomycin C, and vindesine. 19 The intracranial response rates in these studies were 50%, 75.5%, and 56%, while the median survival times were 5.6, 9.7, and 7.6 a b…”
Section: Discussionmentioning
confidence: 98%
“…For many years, WBRT had been standard treatment for BM from NSCLC with OS ranging from 3 to 6 months. The addition of systematic chemotherapy to WBRT was shown to improve outcome for patients with BM from lung cancer, and the median OS was 7.6-8 months (Furuse et al, 1997;Quantin et al, 1999;Moscetti et al, 2007). Gefitinib, as a novel target therapeutic drug, has been commonly used for treating NSCLC in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy leads to a median survival of 3-6 months for patients with BM from NSCLC. Few pilot studies reported that patients with BM from NSCLC treated with chemotherapy concurrently with WBRT had a median OS of 7.6-8 months (Furuse et al, 1997;Quantin et al, 1999;Moscetti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The median survival time was 382 days and the 1-year survival rate was 56.1%, which was considered satisfactory. Furuse et al [11]reported that concurrent WBRT and chemotherapy with cisplatin, vindesine, and mitomycin produced high rates (75.8%) of brain metastasis control and resulted in a median survival of 9.7 months. The response rate in primary lesions was 18%.…”
Section: Discussionmentioning
confidence: 99%